Action Base Learning Pendidikan Kewirausahaan Mahasiswa Maritim - Retnandari, Septina Dwi (PPPM Polimarin, 2025)
This study aims to examine the influence of entrepreneurial spirit and selling practices on the business motivation of maritime students. The background of this study is based on the low motivation of students to become entrepreneurs due to limited practical experience and the lack of internalization of entrepreneurial values in maritime education. The study used a quantitative approach, with 65 students in the maritime education study program in Semarang City as respondents. Data collection was conducted using a closed-ended questionnaire, and data analysis used simple and multiple linear regression with the help of SPSS version 26. The results showed that entrepreneurial spirit significantly influenced selling practices (R² = 84.2%) and business motivation (R² = 84.2%). Furthermore, selling practices also significantly influenced business motivation (R² = 65.7%). Multiple regression showed that entrepreneurial spirit (β = 0.640) and selling practices (β = 0.101) simultaneously contributed to business motivation with a strong correlation (R = 0.747). These findings emphasize the importance of an action-based learning approach in entrepreneurship education to improve the entrepreneurial readiness and spirit of maritime students.